Promoting Recycling: Private Values, Social Norms, and Economic Incentives - Viscusi, W. Kip; Huber, Joel; Bell, Jason (American Economic Review, 2011)
Evidence from a nationally representative sample of households illuminates the determinants of recycling behavior for plastic water bottles. Private values of the environment are influential in promoting recycling, as are personal norms for pro-environmental behavior. However, social norms with respect to the assessment of the household's recycling behaviors by others have little independent effect. Particularly influential are policies that create economic incentives to promote recycling either through state recycling laws that reduce the time and inconvenience costs of recycling or through bottle deposits. Effective policies can have a discontinuous effect at the individual level, transforming non-recyclers into avid recyclers.